Mengatasi Siswa Sekolah Dasar yang Kesulitan dalam Mengerjakan Soal Matematika dengan Pendekatan Segitiga Restitusi - Maryanto Maryanto; Siti Fatimah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
The aim of this research is to describe a model for overcoming elementary school students who have difficulty working on mathematics problems using the restitution triangle approach. Difficulty working on math problems is part of the difficulty learning mathematics. Difficulty learning mathematics is generally defined as a condition where students are unable to learn mathematics subjects completely. The restitution triangle was originally a step towards positively disciplining students. The restitution triangle approach contains aspects of a humanist approach for students. There are three steps to the restitution triangle approach, starting from stabilizing identity. This step builds confidence in students that everyone has experienced mistakes in doing questions. So that students do not feel mentally down. The second step is Validation of Incorrect Actions. In this step, students are invited to reflect on any part of the problem they got wrong and are guided to correct it, there is a remedial learning process. The third step asks about beliefs. In this step, students' motivation is increased so that students now know the steps to work on the questions, and tomorrow they will not make any more mistakes when working on the questions. The results of a literature review found that the stages of the restitution triangle in positive discipline can be used to help overcome elementary school students who have difficulty working on mathematics problems.